STRATEGI PRODUK OLAHAN BUAH ANGGUR SEBAGAI PRODUK UNGGULAN DI KABUPATEN BULELENG PROVINSI BALI - I Gusti Bagus Udayana; Luluk Sulistiyo Budi; Ma’ruf Pambudi Nurwantara (Jurnal Teknologi Industri Pertanian, 2022)
Grapes are a commodity that has high added value. The wide variety of products shows that wine has a highdemand. This study aimed to provide recommendations for alternative priority products for processed Balinesegrapes and optimization strategies in the development of processed grape products in Buleleng Regency. Theresearch method was a survey, observation, focus group discussion, mapping of industrial trees, and AnalyticHierarchy Process (AHP). The results showed that there were 10 existing processed products, and there were 19processed products as alternatives. The priority processed products were wine, jam, and syrup. Matrix internalexternal showed a hold and maintains strategy with an alternative strategy of diversifying wine products by lookingat consumer preferences, producing fine quality and high yield wine, entering the international market, installingpipes to drain water throughout the vineyards, making grape derivative products as unique as possible, training thelabour about wine good production methods, reducing the number of sales of fresh grapes, increasing theproduction of processed grapes for sale, maximizing the promotion of processed wine, forming a market forprocessed wine products through cooperation with companies, governments, and universities, providing labourabout marketing, and forming the institutional structure of the grapes. The priorities of the proposed strategieswere training the labour about marketing, entering the international market, and reducing the number of sales offresh grapes.Keywords: alternative strategies, grapes, industry, processed products